Find the Slope<span> and Y-Intercept y-</span>3=2(x-1). y−3=2<span>(x−1) y - </span>3<span> = </span>2<span> ( x - 1 ). Rewrite in </span>slope<span>-intercept form. Tap for more steps</span>
Answer:
4
Step-by-step explanation:
1 change in x and 4 change in y from 1,0 to 0,4 or 4/1
Answer:
The area after 6 years is ![1519.49km^2](https://tex.z-dn.net/?f=1519.49km%5E2)
<em></em>
Step-by-step explanation:
Given
--- Initial Value
--- Rate
Required
Determine the area after 6 years
Because the area reduces,, the following formula will be used to solve the question.
![y = a*(1 - r)^t](https://tex.z-dn.net/?f=y%20%3D%20a%2A%281%20-%20r%29%5Et)
Here
![t = 6](https://tex.z-dn.net/?f=t%20%3D%206)
So, we have:
![y = 2100*(1 - 5.25\%)^6](https://tex.z-dn.net/?f=y%20%3D%202100%2A%281%20-%205.25%5C%25%29%5E6)
Convert percentage to decimal
![y = 2100*(1 - 0.0525)^6](https://tex.z-dn.net/?f=y%20%3D%202100%2A%281%20-%200.0525%29%5E6)
![y = 2100*(0.9475)^6](https://tex.z-dn.net/?f=y%20%3D%202100%2A%280.9475%29%5E6)
![y = 1519.47866516](https://tex.z-dn.net/?f=y%20%3D%201519.47866516)
-- approximated
<em>The area after 6 years is </em>
<em></em>
Answer:
The given expression is equal to -5
Step-by-step explanation:
Given that:
= (4−3)−6
solving bracket first as 4 -3 equals 1
= 1-6
Subtracting greater term from smaller gives the negative value
= -5
So the given expression will be equal to -5
i hope it will help you!
Answer:
15
Step-by-step explanation:
that's what gogle said